The environmental fate and mobility of oestrogens into soils - Wan Atikah, Wan Omar (2018)
The behaviour of oestrogens in the environment is of great concern due to the endocrine disruption potential. The occurrence of oestrogens is reported as the most potent compounds in the environment, thus this study was conducted to determine the sorption affinity of oestrogens in different types of soils, relationship with between octanol-water partition coefficient and soil-water partititon coefficient of natural and synthetic oestrogen and distribution of oestrogen in environment. The research started with the investigation of the sorption behaviour and factors that influences the sorption behaviour of oestrogens in different type of soils. The sorption behaviour of all oestrogens indicated high association with organic carbon of the soils as sorption capacity increased when organic carbon increased. The value of Kow and Koc used to classify the mobility of oestrogens into soils and as the result, while E2 and EE2 were classified as low to immobile and E1 was slight to low. The values of organic carbon plays an important role in adsorbing an amount of oestrogens in soils. The significant effect on oestrogens’ sorption factors was observed in soils with varied temperature and pH. Based on the analysis, it was clear that the sorption mechanism of oestrogens into soils was physisorption. All the oestrogens indicated a weaker binding to all soils as sorption behaviour of oestrogens onto soils was dependent of their hydrophobicity. The relationship between octanol-water partitioning coefficient (Kow) and soil-water partitioning coefficient (Kd) was being determine from the order of sorption among oestrogens was well correlated with their octanol-water partitioning coefficient (Kow). The higher log Kow values correlated to less mobile organic chemicals into soils. It is believed that hydrophobicity of oestrogens has play a major important role in regulating the sorption of oestrogens in soils. Finally, the result of this study also indicated a considerable difference between experimental values and values generated by the computational model, Estimation Program Interface (EPISUITE). The EPISUITE software underestimate the log Kow value of estrone (E1) but overestimates log Kow 17 ẞ-estradiol (E2) and 17α-ethnylestradiol (EE2). The result also shows that EPISUITE program was overestimated the oestrogens’ partition in soils-environmental compartment. It can be concluded that by inputting the experimental values, the model changed remarkably and has given absolute values to the soil’s ambient conditions. Thus, this study showed that although the computational model was indicative, it did not accurately assess the environmental impact of pollutant. The experiments need to be conducted to obtain the real partitioning of oestrogens in environment.